REGENERASI TANAMAN OBAT KELADI TIKUS (Thyponium flagelliform L. Blume) MELALUI EMBRIOGENESIS SOMATIK SECARA IN VITRO - royani, juwartina ida; Sulistyorini, indah; Utomo, Dwi Rizkyanto (Jurnal Sains dan Teknologi Indonesia, 2012)
Somatic embryogenesis is a process whereby somatic cells have differentiation in somatic embryos and it’s formed from embryonic cells due to the high polarization of uncontrolled cell division. The aim of this research is to produced shoots of rodent tuber via somatic embryos.Induction of somatic embryos from explants in MS media with N (2-chloro-4-pyridyl)-Nphenyl urea (CPPU) and continuous subculture in MS media without plant growth regulator for 1 month. Plantlet regeneration growth in liquid MS media with BAP and IBA fortified with 40 gr/l of sucrose in the dark. The result showed that somatic embryonic appears in media induction after 2 week and plantlet regeneration in 4 week. All plantlet growed from embryosomatic can survive 100% in field with normal shoot.